DINAMIKA CITRA MEREK DAN PREFERENSI PEMBELIAN: Eksplorasi Dalam Konteks Produk Lokal - Mulyati, Yeti (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
Local products have an important role in the regional and national economy. Brand image and purchasing preferences are key factors influencing the acceptance and growth of local products. However, the relationship between brand image and purchase preference in the context of local products is not fully understood. Therefore, this study aims to explore the dynamics of brand image and purchasing preferences for local products. This study aims to identify the extent to which brand image influences consumer purchasing preferences for local products and to explore the factors that moderate this relationship. This study uses a quantitative approach by collecting data through online surveys. The sample consists of consumers who actively buy local products in the city of Bandung. Descriptive statistical analysis and regression analysis were used to examine the relationship between brand image and purchase preference. The results of this study indicate that brand image has a significant influence on local product purchasing preferences. These findings show the complexity of the dynamics between brand image and purchase preferences in the context of local products.